Characterization of a supercoil-dependent S1 sensitive site 5' to the Drosophila melanogaster hsp 26 gene. - Siegfried, E (1986)
We have analyzed the prominent supercoil-dependent S1 nuclease cleavage site 5' to hsp 26 in the plasmid 88B13, which contains 11.7 kilobases from the Drosophila locus 67B1. The double stranded cleavage product is generated by initial nicking on the purine strand, six preferred sites occurring between positions -96 and -90 (relative to the start of transcription) with weaker ones extending to position -84, followed by cleavage on the pyrimidine strand at positions -86 and -84. A derivative of 88B13, 88B13-X, was generated by insertion of an Xho I linker at position -84; this does not affect the positions or strand specificity of the S1 cleavage in that region. A small deletion, delta 41.1, removes the homopurine/homopyrimidine stretch from positions -86 to -132 and is no longer sensitive to cleavage by S1 nuclease 5' to hsp 26. Mung bean and P1 nucleases recognize the same site 5' to hsp 26 and give the same general pattern of cleavage. All three nucleases show an initial cleavage of 88B13 DNA at this site at pH 5.5 but not at pH 6.5, indicating that the DNA structure there may be pH dependent in vitro.